KONTRIBUSI KEKUATAN OTOT LENGAN OTOT PERUT FLEKSIBILITAS TOGOK SERTA DAYA LEDAK OTOT TUNGKAI - Wulandari, Fifit Yeti (Universitas Negeri Surabaya, 2021)
Reject bullets are influenced by physical and engineering factors. Physical condition factors involve components of the body muscles, namely arm muscles, abdominal muscles, flexibility of the togok, as well as explosiveness in the limb muscles, and posture. While the technical factors involve stages such as the way or style used by the bullet repellent, one of which is the backward force (O'Brien style). This study aims to find out how much strength contributes to the arm muscles, to the abdominal muscles, the flexibility of the togok, as well as the explosiveness of the limb muscles, and contributes together strength to the arm muscles, strength in the abdominal muscles, flexibility of the togok, as well as explosiveness in the limb muscles to the results of repulsion pretence in the number of reject bullets using the O'Brien style. This type of research is descriptive research analysis with correlational method approach using coefficient of determination analysis. The population used in this study amounts to 58 students. Sampling techniques using total sampling. Based on the results of the analysis of research data can be found that the contribution of strength in the arm muscles to the results of repulsion achievement in the number of reject bullets using O'Brien style by 21.53%. The contribution of strength in the abdominal muscles to the results of repulsion in bullet reject numbers using O'Brien's style was 20.16%. The contribution of togok flexibility to the results of repulsion performance in the O'Brien-style reject number was 19.27%. The contribution of explosiveness in the limb muscles to the results of repulsion performance in the number of reject bullets using the O'Brien force was 17.14%. And from the double correlation analysis that has been done obtained a double coefficient of determination between the strength of the arm muscles, strength in the abdominal muscles, flexibility of the togok, as well as explosiveness in the limb muscles simultaneously contributed to the results of repulsion achievement in the number of reject bullets using O'Brien style of 45.10%.